Building a Clean Machine : Anti-Corruption Coalitions and Sustainable Reform - Johnston, Michael; Kpundeh, Sahr J. (World Bank, Washington, D.C., 2013)
Many societies have limited corruption through the broad-based mobilization of a diverse range of interests willing and able to defend themselves by making meaningful demands for accountability of, and limits on, official power, and for an end to illicit advantages enjoyed by others. Historically such a process has taken place gradually, as political development has proceeded and the base of participation broadens. But today's high-corruption societies cannot wait for several generations to see such developments take place. The authors argue that social action coalitions, linking public and private actors, are a way to mobilize these sorts of participation and advocacy. Such coalitions are neither a new idea nor a guarantee of successful reforms. In many instances they win out by default as an anti-corruption strategy. But they contend that if sustained by careful planning and a diverse set of incentives, they can reinforce political will and enhance the strength of civil society. Coalition-building efforts are underway in many societies. But too often they have focused only on anti-corruption tactics and pursuing their own growth, rather than looking at the coalition-building process in more general terms. In Part I, the authors employ Wilson's (1973) analysis of the incentives that motivate and reward participation in organizations. This approach helps them identify ways in which the anti-corruption goals can be augmented by other kinds of appeals, even when material incentives are scarce. The authors also identify four stages of the coalition-building process-formation, credibility, expansion, and transformation-in which differing combinations of incentives will be necessary to address the group's most important problems and opportunities. In Part II the authors examine two important coalition-building efforts in light of the discussions thus far-Ghana's Anti-Corruption Coalition, and the Bangalore Agenda Task Force in Bangalore, Karnataka State, India. In Part III the authors link those cases to a broader analysis, suggesting that while purposive incentives are common in the early phases of all coalitions, other varieties must be added to the mix. Wilson's scheme points to ways in which the imaginative use of incentives can aid the transition from one phase of coalition development to the next. The authors conclude with general strategic issues, suggesting ways in which their analysis can be applied to those questions given the important variations to be found among cases.